إدارة النمو وخلق القيمة في المؤسسة الاقتصادية وفق مصفوفة الإستراتيجية المالية - دباح ،كريمة; أقوجيل، أيوب (جامعة الوادي University of Eloued, 2025)
This study aims to analyze both growth and value creation in SaidalGroup for the period (2010-2021) to determine the extent of the group’s ability to achieve actual growth consistent with its sustainable growth andensuring value creation.In order to achieve this goals, the descriptive analytical approach was relied upon, and the financial strategy matrix was used as an analytical tool that combines the economic value added index (EVA) to measure the value and difference between actual sales growth rate (Gsales) and sustainable growth rate (SGR) for growth management. The study found that SaidalGroup in the period (2010-2019) was able to create added value and grew at a rate lower than its SGR, thus occupied the best quadrant (A) in the matrix. However, the continuous decline of both EVA index and SGR led to its transfer to quadrant (B) in the period (2020-2021). this new situation indicates that in subsequent years, SaidalGroupwas needed more external funds to achieve the targeted growth.
Financial Strategy Matrix as a tool for Managing Growth and Creatiing Value in the Organization Case Study of Saidal Group for the Period (2010-2021)
Keywords: إدارة النمو; نمو المؤسسة; خلق القيمة; مصفوفة الإستراتيجية المالية; مجمع صيدال; Growth management; corporate growth; value creation; financial strategy matrix; Saidal Group